2015
DOI: 10.1007/s12029-015-9791-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Annexin A1 and Its Associations with Carcinoembryonic Antigen and Mismatch Repair Proteins in Colorectal Cancer

Abstract: The high incidence of ANXA1 positive expression in colorectal cancer and its association with carcinoembryonic antigen levels might indicate the importance of this protein in the colorectal cancer biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…miR-26a regulated the proliferation and growth of cancer cells by targeting chromodomain helicase DNA binding protein 1 (35), growth regulation by estrogen in breast cancer 1 (35) and β-catenin (36). A number of studies demonstrated that the expression levels of miR-26a decreased in various types of tumor (23,37,38), whereas ANXA1 protein was overexpressed (39)(40)(41). Combined with the results of the present study suggesting that the miR-26a mimic may reduce the expression levels of ANXA1, a negative correlation was identified between miR-26a and ANXA1 in numerous tumors.…”
Section: Discussionsupporting
confidence: 78%
“…miR-26a regulated the proliferation and growth of cancer cells by targeting chromodomain helicase DNA binding protein 1 (35), growth regulation by estrogen in breast cancer 1 (35) and β-catenin (36). A number of studies demonstrated that the expression levels of miR-26a decreased in various types of tumor (23,37,38), whereas ANXA1 protein was overexpressed (39)(40)(41). Combined with the results of the present study suggesting that the miR-26a mimic may reduce the expression levels of ANXA1, a negative correlation was identified between miR-26a and ANXA1 in numerous tumors.…”
Section: Discussionsupporting
confidence: 78%
“…Findings presented here are consistent with the data obtained by Su et al (50), reporting annexin A1 overexpressed in colorectal cancer patients with the K-Ras mutation. Similarly, Ydy et al (57) observed higher levels of annexin A1 in colon but not rectum cancer tissue specimens compared with normal margin tissue.…”
Section: Discussionmentioning
confidence: 85%
“…A number of studies have reported aberrant expression levels of ANXAs in various types of cancer, and that ANXAs may function as tumor suppressors or promoters depending on the cancer type. For example, ANXA1 serves a tumor-promoting role in colorectal and lung cancer (9,10), but functions as a tumor suppressor in esophageal and gastric cancer (11). The role of ANXA1 has also been investigated in hepatocellular carcinoma (HCC), but the results are controversial (12).…”
Section: Introductionmentioning
confidence: 99%